Every man a hero : a memoir of D-Day, the first wave at Omaha Beach, and a world at war /: a memoir of D-Day, the first wave at Omaha Beach, and a world at war. ([2019]) - Lambert, Ray (Arnold Ray); DeFelice, Jim, 1956-
No abstract available